2004
DOI: 10.1073/pnas.0405704101
|View full text |Cite
|
Sign up to set email alerts
|

The roles of latex and the vascular bundle in morphine biosynthesis in the opium poppy, Papaver somniferum

Abstract: The opium poppy, Papaver somniferum, is one of mankind's oldest medicinal plants. Opium poppy today is the commercial source of the narcotic analgesics morphine and codeine. Along with these two morphinans, opium poppy produces approximately eighty alkaloids belonging to various tetrahydrobenzylisoquinoline-derived classes. It has been known for over a century that morphinan alkaloids accumulate in the latex of opium poppy. With identification of many of the enzymes of alkaloid biosynthesis in this plant, bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 34 publications
5
119
2
3
Order By: Relevance
“…However, SalAT and COR transcripts have also been reported in the cytoplasm, or latex, of laticifers (Decker et al 2000;Larkin et al 2007;Allen et al 2008), although in situ hybridization and immunofluorescence labeling failed to detect SalAT and COR mRNA and corresponding enzymes in laticifers (Bird et al 2003;weid et al 2004;Samanani et al 2006). Recently, the application of shotgun proteomics to determine the relative abundance of proteins in isolated latex, or in whole stem including latex, revealed that the final three steps in morphine biosynthesis, catalyzed by T6ODM, COR and CODM, occur primarily in laticifers (Onoyovwe et al 2013).…”
Section: Cellular Localization and Transportmentioning
confidence: 99%
“…However, SalAT and COR transcripts have also been reported in the cytoplasm, or latex, of laticifers (Decker et al 2000;Larkin et al 2007;Allen et al 2008), although in situ hybridization and immunofluorescence labeling failed to detect SalAT and COR mRNA and corresponding enzymes in laticifers (Bird et al 2003;weid et al 2004;Samanani et al 2006). Recently, the application of shotgun proteomics to determine the relative abundance of proteins in isolated latex, or in whole stem including latex, revealed that the final three steps in morphine biosynthesis, catalyzed by T6ODM, COR and CODM, occur primarily in laticifers (Onoyovwe et al 2013).…”
Section: Cellular Localization and Transportmentioning
confidence: 99%
“…1B). Higher-order metabolons, involving direct physical interactions among enzymes, have also been implicated as key control points in many specialized metabolic pathways, including phenylpropanoid, isoprenoid, alkaloid, and cyanogenic glucoside biosyntheses in plants (Achnine et al 2004;Weid et al 2004;Winkel 2004;Jorgensen et al 2005;Leivar et al 2005;Nielsen et al 2008;Chen et al 2011b). Putative metabolons are postulated to facilitate metabolic channeling, thus exerting a level of kinetic control and specificity by localizing spe- cialized pathways within or on the surface of particular subcellular compartments or by balancing the stoichiometry of participating pathway enzymes.…”
Section: Homeostasis and Dynamics In Specialized Metabolismmentioning
confidence: 99%
“…Subsequently, alkaloids are transported to laticifers for storage in large vesicles of the latex. However, a similar study based on the use of polyclonal antibodies to localize BIA biosynthetic enzymes (4'OMT, SalAT, COR, and 7OMT) in resin-embedded tissue sections of opium poppy suggested that laticifers and cells defined as phloem parenchyma are the sites of alkaloid biosynthesis (Weid et al, 2004). An alternative model purported that the early stages of BIA biosynthesis occur in phloem parenchyma cells and that downstream intermediates leading to morphine are transported to laticifers for final biosynthetic transformations and product accumulation.…”
Section: Introductionmentioning
confidence: 99%